Televisi Komunitas: Media Pemberdayaan Masyarakat - Budhi Hermanto (Jurnal Komunikasi, 2007)
Indonesian political changing after 1998 reformation didn't show democratization in the broadcasting and information, on the public side to be exact Actually, the freedom of information has been happen, but the media content is still directed by the media owners, capital and profit, not by the public interest The growing community television, as one of Indonesian broadcasting contemporary phenomena, appears the hope of broadcasting democratization back. The participative ownership and diversity of content become the main points of this media. Community television can play the role of social empowerment media, every information comes from, by and for the community itself. However, some real problems must be solved to develop community television, that are paradigm of community media, resources, technical problems and regulation problems.